Evaluation of International Society on Thrombosis and Hemostasis-Bleeding Assessment Tool (ISTH-BAT) scores in hemophilia patients: Single center experience - Yildirim, Murat; Sayin, Selim; Comert, Melda; Ozgur, Gokhan; Yilmaz, Esra Safak; Ugur, Bilge; Ayli, Meltem (Annals of Medical Research, 2023)
Aim: We aimed to examine the relationship between the clinical bleeding severity classification based on the factor levels and the ISTH-BAT score (calculated numerically over +/- or 10), to evaluate the usability of the ISTH-BAT score in Hemophilia A and B.Materials and Methods: In this retrospective study, the data of hemophilia A and B patients who were administered a face-to-face ISTH-BAT survey upon admission to the outpatient clinic were evaluated. In addition to the positivity rate of the ISTH BAT score of patients with hemophilia, the relationship between this score and the patient's age, hemophilia type and factor level was also evaluated.  Results: The study included 158 male patients (n:125 hemophilia A, n:33 hemophilia B). ISTH-BAT positivity was detected in 45.6% of hemophilia A patients and 57.6% of hemophilia B patients. There were no significant differences between hemophilia A and hemophilia B patients in terms of ISTH-BAT scores (p=0.43). Scores were higher in severe hemophilics, as expected, but there was no statistically significant correlation between factor levels and ISTH-BAT scores in hemophilia A (p=0.56), or hemophilia B (p=0.54).Conclusion: The ISTH-BAT can help recognize individuals with a bleeding history without a diagnosis. However, it does not correlate with factor level in patients with hemophilia and is not effective in determining bleeding susceptibility. Plasma factor levels are the most predictive data for bleeding frequency and severity.
Keywords: Bleeding; Hemostasis; Hemophilia; Score